KAJIAN PENGEMBANGAN RAWA - Ita Minarni (Jurnal Teknologi Berkelanjutan, 2012)
Hydrologic analysis is intended to estimate the presence of water resources taking into account of nature the parameters that influence itself and it is intended to provide an estimate of the amount of water available, the average rainfall areas,is and debit of the amount required swamp puddle in the planning, the preliminary data needed in planning . the purpose of natural resource development system is to regulate wetlands groundwater and to improve the water quality and wetlands that meet the requirements for the cultivation of agricultural and fishery areas. These results indicate that swamp conditions of Kalahien can be developed by taking aspects of hydrology and characteristics of Kalahien swamp area. By using analysis of maximum flow rate expected to be able to design cropping pattern and the right kinds of plants, it can be increasing agricultural productivity. Development step of the are marsh by making zones, fisheries management, maintaining banks of the swamp, use of water weeds and plankton and water quality management also maintain ecosystem sustainability of fish habitat in the mash.